Comparison of intraocular pressure during the application of a liquid patient interface (FEMTO LDV Z8) for femtosecond laser-assisted cataract surgery using two different vacuum levels. Issue 8 (25th May 2017) - Ebner, Martina; Mariacher, Siegfried; Januschowski, Kai; Boden, Katrin; Seuthe, Anna-Maria; Szurman, Peter; Boden, Karl Thomas
Abstract : Background: To evaluate intraocular pressure (IOP) using the application of a novel liquid patient interface for femtosecond laser-assisted cataract surgery with the FEMTO LDV Z8. Methods: IOP was evaluated in enucleated porcine eyes prior, during and after the application of the Femto LDV Z8 liquid patient interface (Ziemer Ophthalmic Systems, Switzerland) using intracameral cannulation (n=20), intravitreal cannulation (n=20), rebound tonometry (n=20) and indentation tonometry (n=20). Pressure was assessed prior vacuum, during vacuum (30 s, 1 min, 2 min, 3 min) and after releasing the vacuum (1 min and 2 min). Two groups with different predefined vacuum levels (350 mbar, 420 mbar) were investigated. Results: Mean intracameral pressure (±SD) increased during vacuum application from 20 mm Hg to 52.00 mm Hg (±6.35mm Hg; p=0.005) and 45.18 mmHg (±4.34 mm Hg; p=0.005) for the 420 mbar and the 350 mbar vacuum levels, respectively. Mean intravitreal pressure increased from 20 mm Hg to 25.60 mm Hg (±9.85 mm Hg; p=0.058) and 28.10 mm Hg (±2.54 mm Hg; p=0.059) for the 420 mbar and the 350 mbar vacuum levels, respectively. Pressure values from indentation and rebound tonometry were in between intracameral and intravitreal values. Mean intracameral IOP was 18.1% higher (p=0.019) in the 420 mbar group compared with the 350 mbar group. Conclusion: During vacuum application of the liquid patient interface of the Femto LDV Z8 for femtosecond laser-assisted cataract surgery, IOP values were higher in the anterior chamber compared with the intravitreal pressure measurements. The higher predefined vacuum level (350 mbar vs 420 mbar) resulted in significant higher intracameral IOP.